Predicting Financial Failure in Indonesian Manufacturing Firms Using Ratio Analysis - Anika Putri; S. Subadriyah (Manunggal Halim Jaya, 2026)
This study aims to examine the impact of financial ratios on financial distress in manufacturing firms listed on the Indonesia Stock Exchange (IDX) for the period 2022–2023. The independent variables analyzed comprise liquidity, profitability, leverage, and activity ratios, while the dependent variable is financial distress. The research utilizes multiple linear regression analysis within a quantitative framework. From a population of 170 companies, purposive sampling was applied to select 23 firms as the sample. Data analysis was performed utilizing SPSS version 25. The results indicated that liquidity, profitability, and activity ratios have a significant negative influence on financial distress, implying that higher levels of these ratios are associated with a reduced risk of distress. Conversely, the leverage ratio demonstrated a significant positive effect on financial distress, indicating that increased dependence on debt heightens the probability of financial difficulties. This study contributes to existing literature and offers important guidance for company management, investors, and creditors in the process of making financial decisions.